2009
DOI: 10.3200/jmbr.41.2.172-192
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and Postural Stability: Review and Hypotheses

Abstract: Among the complications associated with diabetes mellitus is postural control. The authors reviewed 28 studies in the literature that focused on the magnitudes of postural sway that people with and without diabetes exhibit. The general observation is that postural sway is greater for people with diabetes, especially if their condition includes neuropathy. Peripheral sensory neuropathy seems to be the primary factor, but the available evidence does not rule out diabetes per se, other neuropathies (central, auto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
94
0
6

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 104 publications
(107 citation statements)
references
References 93 publications
7
94
0
6
Order By: Relevance
“…Clinical constraints in patients with DN are due to distinct, context-specific instabilities such as movement strategies (hip and ankle) [4] and sensory strategies (specifically somatosensory) [20]. Movement studies have shown that ankle strategy is responsible for slow and small movements of the COM at low velocities but that hip strategy controls larger movements of the COM at higher velocities [21].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Clinical constraints in patients with DN are due to distinct, context-specific instabilities such as movement strategies (hip and ankle) [4] and sensory strategies (specifically somatosensory) [20]. Movement studies have shown that ankle strategy is responsible for slow and small movements of the COM at low velocities but that hip strategy controls larger movements of the COM at higher velocities [21].…”
Section: Discussionmentioning
confidence: 99%
“…This increased risk is presumably due to the well-documented balance problems attributed to neuropathy [1] and sensory ataxia, which is the lack of accurate proprioceptive feedback [2]. Sources of instability in patients with type 2 DN include the loss or reduction of peripheral sensory information in the feet [3][4], the inability of the central nervous system (CNS) to appropriately integrate available postural control information [2,[4][5], and a switch from an ankle-based to a hip-based balance strategy [6][7][8][9][10]. In addition, an increase in the use of vestibular information and dependence on visual information [11] alter the style of postural control in patients with DN.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations